Flacourtia rukam: biochemistry, functions and utilization - Shaari, Khozirah; Lee, Soo Yee (Springer Nature, 2019)
Flacourtia rukam is a species of the Flacourtiaceae. The edible, cherry-like, sweet and sour fruits of the species are not known to be commercially exploited. Phenolic compounds and flavonoids are the main constituents of the fruits, which have also been reported to have good antioxidant properties. However, the available information on the phytochemical and pharmacological aspects of F. rukam indicated it to be very much an underutilized tropical fruit tree. Nevertheless, based on the ethnomedicinal uses of the fruits and other parts of the plant, its economic potential as a health giving food crop should be further investigated and properly evaluated.